Lethal Monkeypox Virus Infection of CAST/EiJ Mice Is Associated with a Deficient Gamma Interferon Response - Earl, Patricia L. (American Society for Microbiology, 2012)
Monkeypox virus (MPXV) is endemic in Africa, where it causes disease in humans resembling smallpox. A recent importation of MPXV-infected animals into the United States raises the possibility of global spread. Rodents comprise the major reservoir of MPXV, and a variety of such animals, even those native to North America, are susceptible. In contrast, common inbred strains of mice, including BALB/c and C57BL/6, are greatly resistant to MPXV. However, several inbred strains of mice derived from wild mice, including CAST/EiJ, exhibit morbidity and mortality at relatively low inoculums of MPXV. Elucidating the basis for the susceptibility of CAST/EiJ mice could contribute to an understanding of MPXV pathogenicity and host defense mechanisms and enhance the value of this mouse strain as a model system for evaluation of therapeutics and vaccines. Here we compared virus dissemination and induced cytokine production in CAST/EiJ mice to those in the resistant BALB/c strain. Following intranasal infection, robust virus replication occurred in the lungs of both strains, although a relatively higher inoculum was required for BALB/c. However, while spread to other internal organs was rapid and efficient in CAST/EiJ mice, the virus was largely restricted to the lungs in BALB/c mice. Gamma interferon (IFN-γ) and CCL5 were induced in lungs of BALB/c mice concomitant with virus replication but not in CAST/EiJ mice. The importance of IFN-γ in protection against MPXV disease was demonstrated by the intranasal administration of the mouse cytokine to CAST/EiJ mice and the resulting protection against MPXV. Furthermore, C57BL/6 mice with inactivation of the IFN-γ gene or the IFN-γ receptor gene exhibited enhanced sensitivity to MPXV.